The pharmacokinetics of cefazolin in patients undergoing elective & semi-elective abdominal aortic aneurysm open repair surgery - Douglas, Alexandra (BioMed Central, 2011)
BACKGROUND: Surgical site infections are common, so effective antibiotic concentrations at the sites of infection are required. Surgery can lead to physiological changes influencing the pharmacokinetics of antibiotics. The aim of the study is to evaluate contemporary peri-operative prophylactic dosing of cefazolin by determining plasma and subcutaneous interstitial fluid concentrations in patients undergoing elective of semi-elective abdominal aortic aneurysm (AAA) open repair surgery. METHODS/DESIGN: This is an observational pharmacokinetic study of patients undergoing AAA open repair surgery at the Royal Brisbane and Women's Hospital. All patients will be administered 2-g cefazolin by intravenous injection within 30-minutes of the procedure. Participants will have samples from blood and urine, collected at different intervals. Patients will also have a microdialysis catheter inserted into subcutaneous tissue to measure interstitial fluid penetration by cefazolin. Participants will be administered indocyanine green and sodium bromide as well as have cardiac output monitoring performed and tetrapolar bioimpedance to determine physiological changes occurring during surgery. Analysis of samples will be performed using validated liquid chromatography tandem mass-spectrometry. Pharmacokinetic analysis will be performed using non-linear mixed effects modeling to determine individual and population pharmacokinetic parameters and the effect of peri-operative physiological changes on cefazolin disposition. DISCUSSION: The study will describe cefazolin levels in plasma and the interstitial fluid of tissues during AAA open repair surgery. The effect of physiological changes to the patient mediated by surgery will also be determined. The results of this study will guide clinicians and pharmacists to effectively dose cefazolin in order to maximize the concentration of antibiotics in the tissues which are the most common site of surgical site infections.